Reflections on the Poetic. Issue 2 (August 2017) - Unknown
Abstract : The texts in this section follow on from a Roundtable discussion at the first CounterText conference, held at Durham University on 18–20 November 2016, on 'The Poetic'. Aside from the papers and readings, the Roundtable had selected participants framing their outlook on the poetic within the context of what they had been hearing at the conference. Five of those outlooks feature here in revised form, together with another offered subsequently. The keywords listed cite only the themes and writers that feature most centrally, or recurrently, across the six pieces.